1984
DOI: 10.1016/0014-5793(84)81067-4
|View full text |Cite
|
Sign up to set email alerts
|

ADP binds similarly to rigor muscle myofibrils and to actomyosin‐subfragment one

Abstract: The binding of MgZ+ ADP to both rabbit skeletal and bovine cardiac myofibrils has been studied at two different temperatures. In each case a single dass of binding sites was observed with a binding constant very close to that reported for the analogous actomyosin-subfra~ent one but much weaker than that seen with the analogous myosin subfragment one alone. These findings are discussed in terms of the constraints on the myosin cross-bridges imposed by the regular array of thick and thin filaments found in myofi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

1985
1985
1996
1996

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 21 publications
3
9
0
Order By: Relevance
“…Therefore, the kinetic mechanism observed for actomyosin-Si may be a reasonable approximation for the mechanism that occurs in muscle undergoing unloaded shortening. The dissociation constant for ADP binding to rabbit psoas and bovine cardiac myofibrils has been measured to be 200 and 7 ,uM, respectively (33). These values are comparable to those for rabbit fast skeletal and bovine cardiac muscle actomyosin-Si in solution, 160 /iM (8,34) and 10 AtM (9), respectively.…”
Section: Discussionsupporting
confidence: 57%
“…Therefore, the kinetic mechanism observed for actomyosin-Si may be a reasonable approximation for the mechanism that occurs in muscle undergoing unloaded shortening. The dissociation constant for ADP binding to rabbit psoas and bovine cardiac myofibrils has been measured to be 200 and 7 ,uM, respectively (33). These values are comparable to those for rabbit fast skeletal and bovine cardiac muscle actomyosin-Si in solution, 160 /iM (8,34) and 10 AtM (9), respectively.…”
Section: Discussionsupporting
confidence: 57%
“…This result is similar to the difference between rabbit psoas and bovine myocardium studied in solutions and myofibrils. It was reported that the MgADP association constant of bovine myocardium is 16 to 29 times larger than that of rabbit psoas (White and Taylor, 1976;Greene and Eisenberg, 1980;Johnson and Adams, 1984;Siemankowski et al, 1985).…”
Section: Comparison With Cardiac Muscle Fibersmentioning
confidence: 96%
“…The Kd values obtained in the present study are much lower than reported before: 50/M (binding of [3H]ADP to turkey gizzard heavy meromyosin; Greene & Sellers, 1987); 100-300 /tM (inhibition of maximal shortening velocity in thiophosphorylated guinea-pig taenia coli fibre; Arner, Hellstrand & Ruiegg, 1987); 200,aM (in vitro motility assay using thiophosphorylated smooth muscle myosin; Warshaw & Trybus, 1991); 18-400 /tM (skeletal muscle;Marston, 1973;Cooke & Pate, 1985;Schoenberg & Eisenberg, 1987;Dantzig et al 1991). On the other hand, Kd values of ADP binding to cross-bridges are also low in cardiac myofibrils (7 AM; Johnson & Adams, 1984). It has been suggested that ADP dissociation from actomyosin S1 is sufficiently slow to limit the unloaded shortening velocity in vertebrate muscle (Siemankowski, Wiseman & White, 1985).…”
Section: High Affinity Mgadp Binding To Cross-bridges In Smooth Musclementioning
confidence: 99%
“…On the other hand, Kd values of ADP binding to cross-bridges are also low in cardiac myofibrils (7 AM; Johnson & Adams, 1984). It has been suggested that ADP dissociation from actomyosin S1 is sufficiently slow to limit the unloaded shortening velocity in vertebrate muscle (Siemankowski, Wiseman & White, 1985).…”
Section: High Affinity Mgadp Binding To Cross-bridges In Smooth Musclementioning
confidence: 99%